# Which products result in a perfect square trinomial? Check all that apply. A=(–x + 9)(–x – 9) B=(xy + x)(xy + x) C=(2x – 3)(–3 + 2x) D=(16 – x2)(x2 – 16) E=(4y2 + 25)(25 + 4y2)

QUESTION POSTED AT 18/01/2020 - 07:11 AM

QUESTION POSTED AT 18/01/2020 - 07:11 AM

The *correct answers* are:

B=(xy + x)(xy + x) ; C=(2x – 3)(–3 + 2x) ; and E=(4y² + 25)(25 + 4y²)

**Explanation**:

In order to have a perfect square trinomial, we must multiply two binomials that are exactly the same. For (xy+x)(xy+x), are multiplying two identical binomials.

For (2x-3)(-3+2x), we are multiplying two binomials that are the same but written in a different order. The same is true of (4y² + 25)(25 + 4y²).

F(x) = -85x + 3145...the domain is going to be the x value while the range is the f(x) value.

answer is going to be all whole numbers from 0 to 37

notice if u sub in 37 for x.....

f(37) = -85(37) + 3145

f(37) = - 3145 + 3145

f(37) = 0...that means after 37 minutes, there are no un-printed pages...all the pages have been printed. So ur answer would be greater then 0, but less then or equal to 37.....and they have to be whole numbers.....they cant be all real number because that includes irrational numbers.

answer is going to be all whole numbers from 0 to 37

notice if u sub in 37 for x.....

f(37) = -85(37) + 3145

f(37) = - 3145 + 3145

f(37) = 0...that means after 37 minutes, there are no un-printed pages...all the pages have been printed. So ur answer would be greater then 0, but less then or equal to 37.....and they have to be whole numbers.....they cant be all real number because that includes irrational numbers.

ANSWERED AT 16/02/2020 - 07:04 PM

QUESTION POSTED AT 16/02/2020 - 07:04 PM

6.) y - (-3) = (1 - (-3))/(3 - 1) (x - 1)

y + 3 = (1 + 3)/2 (x - 1)

y + 3 = 4/2 (x - 1)

y + 3 = 2(x - 1) = 2x - 2

y = 2x - 2 - 3 = 2x - 5

y = 2x - 5

y + 3 = (1 + 3)/2 (x - 1)

y + 3 = 4/2 (x - 1)

y + 3 = 2(x - 1) = 2x - 2

y = 2x - 2 - 3 = 2x - 5

y = 2x - 5

ANSWERED AT 16/02/2020 - 07:04 PM

QUESTION POSTED AT 16/02/2020 - 07:04 PM

Note that 1 - cos(x) = 2sin²(x/2)

⇒ lim x→0 xtan(x)/ [1 - cos(x)] =

= lim x→0 xtan(x) / 2sin²(x/2) =

= lim x→0 1/2 xtan(x) / [sin²(x/2) / (x/2)² * (x/2)²]

Also, we know that lim x→0 sin(x)/x = lim x→0 tan(x)/x = 1

So the limit is :

= 1/2 lim x→0 xtan(x) / (x²/4) =

= 1/2 lim x→0 4/x² * xtan(x) =

= 2 lim x→0 tan(x)/x =

= 2.

I hope my answer has come to your help. Thank you for posting your question here in Brainly. We hope to answer more of your questions and inquiries soon. Have a nice day ahead!

⇒ lim x→0 xtan(x)/ [1 - cos(x)] =

= lim x→0 xtan(x) / 2sin²(x/2) =

= lim x→0 1/2 xtan(x) / [sin²(x/2) / (x/2)² * (x/2)²]

Also, we know that lim x→0 sin(x)/x = lim x→0 tan(x)/x = 1

So the limit is :

= 1/2 lim x→0 xtan(x) / (x²/4) =

= 1/2 lim x→0 4/x² * xtan(x) =

= 2 lim x→0 tan(x)/x =

= 2.

I hope my answer has come to your help. Thank you for posting your question here in Brainly. We hope to answer more of your questions and inquiries soon. Have a nice day ahead!

ANSWERED AT 16/02/2020 - 06:43 PM

QUESTION POSTED AT 16/02/2020 - 06:43 PM

The answer to the problem is as follows:

The square root of -15 is equal to i*sqrt(15). Therefore, the conjugate of this complex number is -i*sqrt(15).

I hope my answer has come to your help. Thank you for posting your question here in Brainly. We hope to answer more of your questions and inquiries soon. Have a nice day ahead!

The square root of -15 is equal to i*sqrt(15). Therefore, the conjugate of this complex number is -i*sqrt(15).

I hope my answer has come to your help. Thank you for posting your question here in Brainly. We hope to answer more of your questions and inquiries soon. Have a nice day ahead!

ANSWERED AT 16/02/2020 - 06:43 PM

QUESTION POSTED AT 16/02/2020 - 06:43 PM

So the goal here is to find the value of "w". The first thing you must do is transpose the number 9 to the side of -7 and it would look like this, 4w = -7 - 9. Change the positive sign of the number 9 to negative when you transpose. Then, the equation will be simplified and it will look like this, 4w = -16. Then lastly, to get the value of "w", you must divide the equation to 4 and it will be like this,

__4w__ = __-16 __ so you will get the answer w = -4. I hope this helps you

4 4

ANSWERED AT 16/02/2020 - 06:42 PM

QUESTION POSTED AT 16/02/2020 - 06:42 PM

The correct answer is $6000.00

ANSWERED AT 16/02/2020 - 06:42 PM

QUESTION POSTED AT 16/02/2020 - 06:42 PM

**Answer:**

**Option b is correct**

**Step-by-step explanation:**

**Given** the polynomial

we have** to find the set of possible rational roots for the polynomial.**

**Rational root theorem states that if P(x) has any rational roots then they must be of form **

Here

Factors of 10=1, 2, 5, 10

Factors of 2=1, 2

**Possible rational roots are**

**Option b is correct**

ANSWERED AT 16/02/2020 - 06:41 PM

QUESTION POSTED AT 16/02/2020 - 06:41 PM

We can solve the given equation above by doing the completing the square method. We do as follows:

x^2 + 6x = 10

x^2 + 6x + 9 = 10 +9

(x+3)^2 = 19

√(x+3)^2 = √19

x + 3 = √19

Therefore, the correct answer from the choices listed above is the third option, -3 ± sqrt 19. Hope this answers the question. Have a nice day.

x^2 + 6x = 10

x^2 + 6x + 9 = 10 +9

(x+3)^2 = 19

√(x+3)^2 = √19

x + 3 = √19

Therefore, the correct answer from the choices listed above is the third option, -3 ± sqrt 19. Hope this answers the question. Have a nice day.

ANSWERED AT 16/02/2020 - 06:40 PM

QUESTION POSTED AT 16/02/2020 - 06:40 PM

**Answer:**

**No, it is 3x-5 and r=0**

**Step-by-step explanation:**

We can do it by long division method the required quotient is 3x-5 and r=0

not 3x-1 , r=1

multiply the divisor with 3x we will get to cancel out the first term of dividend

Now after solving we will get

Now, multiply the divisor by -5 we will get -5x-15 which will cancel the entire dividend.

ANSWERED AT 16/02/2020 - 06:37 PM

QUESTION POSTED AT 16/02/2020 - 06:37 PM

The function n^3/1000 - 100n^2 - 100n + 3. The big-Theta notation represents a function that can sandwich the given function for sufficiently large n. Formally, Theta(g(n): k1*g(n) < f(n) < k2*g(n). Sometimes, it is just as easy as removing the lower order terms and dropping the coefficient of the highest degree term. Thus, the function can be represented as Theta(n^3).

I hope my answer has come to your help. Thank you for posting your question here in Brainly. We hope to answer more of your questions and inquiries soon. Have a nice day ahead!

I hope my answer has come to your help. Thank you for posting your question here in Brainly. We hope to answer more of your questions and inquiries soon. Have a nice day ahead!

ANSWERED AT 16/02/2020 - 06:35 PM

QUESTION POSTED AT 16/02/2020 - 06:35 PM

The solution to the problem is as follows:

For 3 notebooks you pay $1.98 so the ratio is 1:0.66.

For 10 notebooks, then we could scale the ratio and it will become 10:6.60. So they will cost you $6.60.

I hope my answer has come to your help. Thank you for posting your question here in Brainly. We hope to answer more of your questions and inquiries soon. Have a nice day ahead!

For 3 notebooks you pay $1.98 so the ratio is 1:0.66.

For 10 notebooks, then we could scale the ratio and it will become 10:6.60. So they will cost you $6.60.

I hope my answer has come to your help. Thank you for posting your question here in Brainly. We hope to answer more of your questions and inquiries soon. Have a nice day ahead!

ANSWERED AT 16/02/2020 - 06:35 PM

QUESTION POSTED AT 16/02/2020 - 06:35 PM

**Answer: No,** **the line through points P(–8, –10) and Q(–5, –12) is not perpendicular to the line through points R(9, –6) and S(17, –5).**

**Step-by-step explanation:**

Two lines are called perpendicular to each other if the product of their slope is -1.

Since, the slope of a line having end points and is,

Thus, the slope of line Joining points P(–8, –10) and Q(–5, –12),

While, The slope of line Joining points R(9, –6) and S(17, –5),

Since,

Thus, **the line through points P(–8, –10) and Q(–5, –12) is not perpendicular to the line through points R(9, –6) and S(17, –5).**

ANSWERED AT 16/02/2020 - 06:35 PM

QUESTION POSTED AT 16/02/2020 - 06:35 PM

In the points ( -5 , 0) , ( -4 , 2) , (0 , 10) , and (3 , 16)

-5, -4, 0, and 3 are the domains

ANSWERED AT 16/02/2020 - 06:23 PM

QUESTION POSTED AT 16/02/2020 - 06:23 PM

B. 3:40

You would have to add 25 minutes to 3:15 to get 3:40

ANSWERED AT 16/02/2020 - 06:21 PM

QUESTION POSTED AT 16/02/2020 - 06:21 PM

Solve for x by simplifying both sides of the equation, then isolating the variable.

x = -54

x = -54

ANSWERED AT 16/02/2020 - 06:20 PM

QUESTION POSTED AT 16/02/2020 - 06:20 PM

**Answer:**

**B.** Division

**Step-by-step explanation:**

We have been given an expression . We are asked to determine which operation will we use first to simplify our given expression.

Using order of operations PEMDAS, we will remove parenthesis first. To remove parenthesis, we need to simplify .

**Therefore, we will use division first to simplify our given expression.**

ANSWERED AT 16/02/2020 - 06:17 PM

QUESTION POSTED AT 16/02/2020 - 06:17 PM

Μ = 64

σ = 3.5

a)

μ - 3σ = 53.5

μ - 2σ = 57.0

μ - σ = 60.5

μ = 64.0

μ + σ = 67.5

μ + 2σ = 71.0

μ + 3σ = 74.5

b)

(71 - 64)/3.5 = 2.0

z = 0.9772

n = 3000*(1 - 0.9772)

≈ 68

Hope this helps!

σ = 3.5

a)

μ - 3σ = 53.5

μ - 2σ = 57.0

μ - σ = 60.5

μ = 64.0

μ + σ = 67.5

μ + 2σ = 71.0

μ + 3σ = 74.5

b)

(71 - 64)/3.5 = 2.0

z = 0.9772

n = 3000*(1 - 0.9772)

≈ 68

Hope this helps!

ANSWERED AT 16/02/2020 - 06:10 PM

QUESTION POSTED AT 16/02/2020 - 06:10 PM

I think that would be 0.02792 I'm thinking and trying to work it out

ANSWERED AT 16/02/2020 - 06:07 PM

QUESTION POSTED AT 16/02/2020 - 06:07 PM

**Answer with explanation:**

Consider the geometrical shape , which is in the first Quadrant

**Option 1: **

A reflection across the y-axis, followed by a reflection across the x-axis, and then a 90° clockwise rotation about the origin .

**Explanation: **

When we reflect the shape across y axis , it will reach in second Quadrant, then by reflection across the x-axis,takes it to the third Quadrant,then a 90° clockwise rotation about the origin takes it to the second Quadrant.

**Option 2: **

a 90° clockwise rotation about the origin and then a 180° rotation about the origin

**Explanation: **

90° clockwise rotation about the origin, takes the shape to fourth Quadrant,and then a 180° rotation about the origin takes the shape to Second Quadrant.

**Option 3**

a reflection across the x-axis, followed by a 90° counterclockwise rotation about the origin, and then a reflection across the x-axis

**Explanation:**

a reflection across the x-axis, takes the shape in fourth Quadrant,then a 90° counterclockwise rotation about the origin takes the shape in first Quadrant, and again then a reflection across x axis ,takes the shape again in Fourth Quadrant.

**Option 4**

a 90° counterclockwise rotation about the origin

**Explanation:**

a 90° counterclockwise rotation about the origin takes the shape in Second Quadrant.

**Option 3 That is , Statement 3,⇒ a reflection across the x-axis, followed by a 90° counterclockwise rotation about the origin, and then a reflection across the x-axis, is not equivalent to the other statement.**

ANSWERED AT 16/02/2020 - 06:07 PM

QUESTION POSTED AT 16/02/2020 - 06:07 PM

(19/6)/(9/10)=95/27

(13/3)/(4/7)=91/12

(13/3)/(4/7)=91/12

ANSWERED AT 16/02/2020 - 06:07 PM

QUESTION POSTED AT 16/02/2020 - 06:07 PM

The answer is x=31 over 13

ANSWERED AT 16/02/2020 - 05:54 PM

QUESTION POSTED AT 16/02/2020 - 05:54 PM

The continuity condition demands that the value of the function at x =0 equals the limi of the function as x ->0

As x -> 0, Limit of [sin (x) / x ] = 1.

Then, given that f(0) = k , k must be 1.

**Answer: k must be 1.**

As x -> 0, Limit of [sin (x) / x ] = 1.

Then, given that f(0) = k , k must be 1.

ANSWERED AT 16/02/2020 - 05:36 PM

QUESTION POSTED AT 16/02/2020 - 05:36 PM

If the base is on the x-axis, the width of the rectangle is = xif the height is based on the parabola, the length = 7-x^2

the area of a rectangle = length * width

thus, area = x*(7-x^2)= 7x-x^3

in order to maximize the area, you would need to take the derivative of the area and set it equal to 0

Area = 7x-x^3Area' = 7 - 3x^2

7-3x^2 = 0thus, x = 1.5275

this x represents the x needed to create the largest possible area with the given parameters.

Thus:Width (x-axis) = 1.5275Length (y-axis) = 7 - (1.5275)^2 = 4.6667

the area of a rectangle = length * width

thus, area = x*(7-x^2)= 7x-x^3

in order to maximize the area, you would need to take the derivative of the area and set it equal to 0

Area = 7x-x^3Area' = 7 - 3x^2

7-3x^2 = 0thus, x = 1.5275

this x represents the x needed to create the largest possible area with the given parameters.

Thus:Width (x-axis) = 1.5275Length (y-axis) = 7 - (1.5275)^2 = 4.6667

ANSWERED AT 16/02/2020 - 05:35 PM

QUESTION POSTED AT 16/02/2020 - 05:35 PM

I can be wrong, but I think that the answer is: To find the values of p, q, r and s, you should start by finding all factor **pairs** of the leading coefficiant and constant term.

ANSWERED AT 16/02/2020 - 05:35 PM

QUESTION POSTED AT 16/02/2020 - 05:35 PM

To know if the given matrix is one to one linear transformation, Row reduce the Matrix A and if it has free variables in it it means it is not a one to one linear transformation.

So, we take A and apply Row Operation and get the following matrix

1 0 0

0 1 0

0 0 0

As, it has free variables in it, it means it is not a one to one linear transformation.

Hope it helps :)

So, we take A and apply Row Operation and get the following matrix

1 0 0

0 1 0

0 0 0

As, it has free variables in it, it means it is not a one to one linear transformation.

Hope it helps :)

ANSWERED AT 16/02/2020 - 05:34 PM

QUESTION POSTED AT 16/02/2020 - 05:34 PM

The extrema of a function happen when the derivative is equal to zero. So first we calculate the derivative:R′(x)=100−0.4x

And then we solve:0=100−0.4x

0.4x=100

x=250 units

Now we can substitute back into the original equation to calculate the revenue:R(250)=100(250)−0.2(2502)

R(250)=$12500

And then we solve:0=100−0.4x

0.4x=100

x=250 units

Now we can substitute back into the original equation to calculate the revenue:R(250)=100(250)−0.2(2502)

R(250)=$12500

ANSWERED AT 16/02/2020 - 05:33 PM

QUESTION POSTED AT 16/02/2020 - 05:33 PM

Let

y------> one number

x-----> another number

we know that

------> equation A

------> equation B

substitute equation A in equation B

Find the value of y

the numbers are and

therefore

__the answer is the option B__

** and **

ANSWERED AT 16/02/2020 - 05:32 PM

QUESTION POSTED AT 16/02/2020 - 05:32 PM

The answer is

D. y = 4cos(-x) - 2

proof

cosine is an even function, it means cos(-x) = cosx

so y = 4cos(-x) - 2 = y = 4cos(x) - 2

D. y = 4cos(-x) - 2

proof

cosine is an even function, it means cos(-x) = cosx

so y = 4cos(-x) - 2 = y = 4cos(x) - 2

ANSWERED AT 16/02/2020 - 05:32 PM

QUESTION POSTED AT 16/02/2020 - 05:32 PM

**Answer:**

**Step-by-step explanation:**

alright lets get started.

the linear combination is given by :

foiling 4 and 2 into the parenthesis

Combinig x and y terms together

** : answer**

Hope it will help. :)

ANSWERED AT 16/02/2020 - 05:32 PM

QUESTION POSTED AT 16/02/2020 - 05:32 PM

2. n = 8 (Identity property)

3. n = 0 (Zero Property)

4. n = 22 (Additive Identity Property)

5. n = 4 (Fractal property)

3. n = 0 (Zero Property)

4. n = 22 (Additive Identity Property)

5. n = 4 (Fractal property)

ANSWERED AT 16/02/2020 - 05:29 PM

QUESTION POSTED AT 16/02/2020 - 05:29 PM